La evaluación del desempeño como factor influyente en la formación profesional del docente universitario. - Lalangui Pereira, Julio Honorato; Valarezo Castro, Jorge Washington; Fernández, Homero Patricio (My University, 2019)
The objective of this paper is to analyze the process of evaluation of teaching performance as an influential factor in professional training. To achieve this goal, we start with experiences and innovations that allows this practice to be carried out in accordance with the new tendencies of the 21st century teacher. Such processes lead to adopt conceptions of teacher evaluation from a critical, reflective and transformative view, which is an essential activity to improve classroom processes and consequently the quality of education. The methodology used responds to the quantitative-qualitative paradigm, where the use of the methods was specified: descriptive, explanatory, analytical and synthetic; and a questionnaire structured according to the Likert scale was applied to 28 teachers from Basic Education Program of the “Universidad Técnica de Machala”. Among the findings, it was found that it is a systematic and obligatory practice that leads to decision-making to improve educational quality; from this perspective, it is concluded that the evaluation of performance has allowed it to reconcile the interest for the qualitative improvement of education with the demands of an efficient management of teaching.
El presente trabajo de tiene como objetivo analizar el proceso de evaluación del desempeño docente como factor influyente en la formación profesional. Para lograr esta finalidad se parte de experiencias e innovaciones que permita efectivizar esta práctica en función de las nuevas tendencias del docente siglo XXI. Tales procesos conllevan a adoptar concepciones de la evaluación docente a partir de una visión crítica, reflexiva y transformadora, lo que constituye una actividad esencial para mejorar procesos áulicos, y en consecuencia la calidad educativa. La metodología empleada responde al paradigma cuanti-cualitativo, donde se precisó el empleo de los métodos: descriptivo, explicativo, analítico y sintético; y se aplicó un cuestionario estructurado de acuerdo a la escala de Likert a 28 docentes de la Carrera de Educación Básica de la Universidad Técnica de Machala. Entre los hallazgos se encontró que es una práctica sistemática y obligatoria que conlleva a la toma de decisiones para mejorar la calidad educativa; desde esta perspectiva se concluye que la evaluación del desempeño ha permitido conciliar el interés por la mejora cualitativa de la educación con las exigencias de una gestión eficiente de la docencia.
Keywords: EVALUACIÓN; DESEMPEÑO; DOCENTE; FORMACIÓN PROFESIONAL